Unveiling Utopian Civic Engagement: Empowering Digital Natives through Digital Literacy for a Better Future - Deni Zein Tarsidi; Karim Suryadi; Dasim Budimansyah; Rahmat Rahmat (IJRAEL: International Journal of Religion Education and Law, 2023)
This study aims to uncover the potential of empowering digital natives through digital literacy to strengthen utopian civic engagement for a better future. The research methodology employed in this study is grounded theory, with data collected through in-depth interviews with 15 digital natives respondents in Bandung, Indonesia. The collected data was then analyzed using NVivo version 12 Plus for Macbook software. The study's findings indicate that digital literacy promotes positive social media use and enhances digital natives' civic engagement. Digital natives with high digital literacy tend to have greater social and political awareness, enabling them to identify and address complex social issues through active participation in online discussions and actions. Furthermore, digital literacy helps shape their civic identity and a sense of belonging to online communities. The conclusion of this research provides a deeper understanding of the potential for empowering digital natives through digital literacy for utopian civic engagement.